KESUKSESAN SISTEM TEKNOLOGI INFORMASI PADA E-COMMERCE - Widaryanti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2008)
E-commerce is using computer for facilitate all of operational enterprise. A lot of operational enterprise have attribute to internal finance, human resources, information service, and marketing. Others operation included company relation with all of eight circle element. What is the most hoped from information technology system application in e-commerce? If this question inquired to organizations who application information technology system, they will answer the most important is that information technology system success in their implementation. What is the success of information technology system? How can make the success of information technology system?Many research have done to identification factors that evoke the success of information technology system. DeLone and McLean‘s research can be reference to make information technology system success  in organization, that is: system quality, information quality, use, user satisfaction, individual impact, and organizational impact.